The Conditions of Functioning of the Student Family in Modern Russia: The Main Problems and Resources of Well-Being - T. K. Rostovskaya; E. N. Vasilieva; V. S. Nikolskiy (Высшее образование в России, 2024)
The research relevance of the of the Institute of student families is growing in the Russian Federation. Firstly, a student family is an object of social protection since the conditions of its functioning are associated with a number of problems. Therefore, resources are needed to form or restore well-being. Secondly, due to the decrease in the overall fertility rate and population in Russia student families can be considered as a demographic development resource. This study discusses well-being parameters of different types of student families. The purpose of this work is to systematize these parameters that determine the well–being of student families, which will allow us to draw conclusions about what resources families need. At the first stage, a theoretical analysis was carried out and definitions of the concept of “student family” were clarified. At the second stage of the study, sociological data were collected by a mass survey and factor analysis (the method of main components, Kaiser normalization) was carried out, which allowed us to determine the trends of student youth goal-setting. These goals underlie the formation of ideas about well-being. The methodological basis of the research is the theory of planned behavior, which allows us to consider the attitudes of student youth as significant for members of student families who are included in the social environment of the higher education space. As a result, it was revealed which attitudes are the basis for the formation of well-being. Empirical data were obtained within the framework of the All-Russian sociological study “Student Family of Russia” conducted by IDI FNIST RAS in 2022, the sample size was 1,388 students aged 17-28 years receiving higher professional education in 15 higher educational institutions in 12 regions of Russia. The study identified the historical conditions for changes in the institution of the student family and parameters of well-being and described different types of student families.